RECONSTRUCTION OF SANDUR PERFORMANCE AT SANDUR SEDHET SREPET IN BOJONEGORO - Indra Cahya, Bagus; Hidajad, Arif (Solah, 2025)
Sandur Sedhet Srepet is one of the Sandur groups that still exist in Bojonegoro Regency. This group is present in the community to strengthen the position of Sandur by rearranging the form of Sandur performances without composing the contents contained therein and adapting to the times. This group is led by young people, creating, and rearranging the form of Sandur peformances so that they can be well received by the community. The researcher took the problem formulation (1) How to reconstruct the form of Sandur Sedhet Srepet performances in preserving Sandur Bojonegoro. This research theory uses the theory od reconstruction. This research uses a qualitative approach. Data collection uses (1) Observation Techniques, (2) Interview Techniques, and (3) Documentation Techniques. The results of the study show that the reconstruction of the Sandur performance in the Sandur Sedhet Srepet group contains differentiation, namely differences with the previous form. The second stage is desacralization by reducing or eliminating sacred forms. The third stage is deterritorialization, namely the expansion or spread. The fourth stage is distortion, namely the reduction or cutting. The last stage is degradation or a decrease in value.